2016
DOI: 10.2495/cmem-v4-n2-165-175
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of magnetic resonance imaging, electrical impedance tomography and ultrasonic doppler velocimetry for semi-dilute fibre flow suspension characterisation

Abstract: Experimental comparisons between imaging techniques serve to provide confidence in the validity of each technique for the study of multiphase flow systems. Such cross-validation can establish the limitations of each technique quantitatively. In the present paper, the authors report efforts made on the characterization of semi-dilute, mono-dispersed suspensions of rayon fibres in turbulent water flow using Magnetic Resonance Imaging (MRI), Ultrasound Velocity Profiling (UVP) and Electrical Impedance Tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Alternative techniques can be used to measure velocity profiles in such concentrated suspensions. For instance, Faia et al [6] have shown a good agreement between the results using MRI, electrical impedance tomography, and ultrasonic Doppler velocimetry in their study of fiber suspensions.…”
mentioning
confidence: 88%
“…Alternative techniques can be used to measure velocity profiles in such concentrated suspensions. For instance, Faia et al [6] have shown a good agreement between the results using MRI, electrical impedance tomography, and ultrasonic Doppler velocimetry in their study of fiber suspensions.…”
mentioning
confidence: 88%
“…Figure26. Nuclear magnetic resonance tomography system schematics (left) and velocity profile measured in water-rayon fiber flow (right) (adapted from[134] and taken from[161], respectively).…”
mentioning
confidence: 99%